Analysis Of Financial Performance And Macroeconomic On Firm Value - Savira Faradila; Kharisya Ayu Effendi (Jurnal Manajemen, 2023)
The purpose of this study is to determine the impact of capital structure, profitability, and gross domestic product on the firm value of food and beverage companies listed on the Indonesia Stock Exchange (BEI) from 2015 to 2021. Thirty-three food and beverage companies comprised the total population of this research; after selecting samples using sampling techniques, thirteen companies were obtained for use as samples in this study. Multiple linear regression analysis with panel data from 2015 to 2021 is utilized in this study. Results indicated that capital structure has no effect on firm value, profitability has a positive and significant effect on firm value, and GDP has no effect on firm value.